2010
DOI: 10.1534/genetics.110.115543
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Population Structure and Environmental Associations to Aridity Across the Range of Loblolly Pine (Pinus taedaL., Pinaceae)

Abstract: Natural populations of forest trees exhibit striking phenotypic adaptations to diverse environmental gradients, thereby making them appealing subjects for the study of genes underlying ecologically relevant phenotypes. Here, we use a genome-wide data set of single nucleotide polymorphisms genotyped across 3059 functional genes to study patterns of population structure and identify loci associated with aridity across the natural range of loblolly pine (Pinus taeda L.). Overall patterns of population structure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
403
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(431 citation statements)
references
References 100 publications
24
403
0
4
Order By: Relevance
“…Quaternary climate changes have also been hypothesized to have driven the decline of a now-extinct species of Picea in the southeastern United State, far outside of the ice sheet distribution (Jackson and Weng, 1999). Thus, current P. angustifolia genetic subdivision likely reveals the existence of multiple Pleistocene populations, similar to hypotheses about P. trichocarpa (Slavov et al, 2012), P. balsamifera (Breen et al, 2012) and Pinus taeda (Eckert et al, 2010). Among these P. angustifolia subpopulations, however, N e changes in the recent past reflect drastically different impacts of western North America climate.…”
Section: Population Structuresupporting
confidence: 65%
See 1 more Smart Citation
“…Quaternary climate changes have also been hypothesized to have driven the decline of a now-extinct species of Picea in the southeastern United State, far outside of the ice sheet distribution (Jackson and Weng, 1999). Thus, current P. angustifolia genetic subdivision likely reveals the existence of multiple Pleistocene populations, similar to hypotheses about P. trichocarpa (Slavov et al, 2012), P. balsamifera (Breen et al, 2012) and Pinus taeda (Eckert et al, 2010). Among these P. angustifolia subpopulations, however, N e changes in the recent past reflect drastically different impacts of western North America climate.…”
Section: Population Structuresupporting
confidence: 65%
“…Ingvarsson (2008) and Ma et al (2010) found support for models of population bottlenecks and expansion in P. tremula, as did Keller et al (2010) in a sample of P. balsamifera, and Zhou et al (2014) in P. trichocarpa. Outside of regions covered by Pleistocene ice, Eckert et al (2010) found evidence of expansion from multiple refugia for Pinus taeda based on patterns of population structure. Although these studies have found evidence of expansion since the LGM, warming and drying of southern range portions could reduce regional suitability for some species, leading to population contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Local adaptation to arid environments despite high levels of gene flow Weak patterns of population structure and high historical gene flow estimates between distant populations were found for P. canariensis, consistent with high contemporary gene flow by pollen and seed (Ló pez de Heredia et al, 2010) and for other coniferous species Eckert et al, 2010b). Molecular studies based on chloroplast DNA variation have revealed that gene flow is significant along elevational transects (Navascués and Emerson, 2007) but that some level of genetic differentiation, suggested by the presence of private chloroplast DNA haplotypes, was maintained among valleys (Gó mez et al, 2003).…”
Section: Evolution Of P Canariensis Is Driven By Volcanic Activitysupporting
confidence: 54%
“…Our results suggest that ecologically relevant selective forces were involved in population adaptive divergence of R. oldhamii. Spatial heterogeneity in environmental variables, revealed by the multivariate analysis of variance, is expected to cause genetic divergence among populations, which may create sufficient variations in fitness-related traits and the consequent formation of local adaptations (for example, Eckert et al, 2010).…”
Section: Ecologically Relevant Adaptive Divergencementioning
confidence: 99%